PSEUDO SHARIAH ECONOMY AND MUSLIM’S CIVILIZATION DEBT - Tono Saksono (Penerbit UTHM, 2014)
This book discusses the defect of the current practice of shariah economy viewed from the fact that Muslims apparently have forgotten the use of the Islamic calendar as the basis of the accounting system of their businesses. The use of the Gregorian calendar as a replacement of the inexistence of a reliable Islamic calendar seems to have created trivial problems. However, this book will show, the ostensibly trivial problem has actually snowballed into a huge problem that all Muslims in the world have to bear now. The use of the Gregorian calendar as the basis of Muslims’ accounting system has inadvertently created accumulated zakat payment deficit. By reading this book, it is of paramount importance that Muslims become aware of the past mistakes in neglecting the use of the Islamic calendar in our worldly lives.